How do men perceive erectile dysfunction and its treatment? A qualitative study on opinions of men - Low, W.Y.; Ng, C.J.; Choo, W.Y.; Tan, H.M. (2006)
Introduction. Erectile dysfunction (ED) is a common medical disorder affecting the aging male. A man's perception of a disease affects his health seeking behaviour. This study aimed to explore perceptions of ED among men with ED and how these perceptions came about. Methods. This qualitative study utilized in-depth interviews involving 17 urban men aged between 40 and 75 years old. Results. Misconceptions existed regarding the definitions of ED. Most men perceived impotence to be more serious than ED. Although most were aware of the medical causes of ED, 'overuse of penis' and black magic were mentioned as culturally-related causes. ED was perceived as a serious problem associated with loss of manhood and it had a significant impact on relationships with their partners. However, some adopted an 'accepting' view and attributed it to aging and fate. Most men were only familiar with PDE-5 inhibitors and traditional therapies. PDE-5 inhibitors were perceived to be effective but they were concerned about side effects and costs. Conclusions. Identifying men's perceptions of ED and its treatment would help doctors in their consultation, and inform health policy makers in planning appropriate public education and services.